CRISPRi-mediated characterization of novel anti-tuberculosis targets: Mycobacterial peptidoglycan modifications promote beta-lactam resistance and intracellular survival - Silveiro, Cátia; Marques, Mariana; Olivença, Francisco; Pires, David; Mortinho, Diana; Nunes, Alexandra; Pimentel, Madalena; Anes, Elsa; Catalão, Maria João (Frontiers in Cellular and Infection Microbiology, 2023)
The lack of effective therapeutics against emerging multi-drug resistant strains of Mycobacterium tuberculosis (Mtb) prompts the identification of novel anti-tuberculosis targets. The essential nature of the peptidoglycan (PG) layer of the mycobacterial cell wall, which features several distinctive modifications, such as the N-glycolylation of muramic acid and the amidation of D-iso-glutamate, makes it a target of particular interest. To understand their role in susceptibility to beta-lactams and in the modulation of host-pathogen interactions, the genes encoding the enzymes responsible for these PG modifications (namH and murT/gatD, respectively) were silenced in the model organism Mycobacterium smegmatis using CRISPR interference (CRISPRi). Although beta-lactams are not included in TB-therapy, their combination with beta-lactamase inhibitors is a prospective strategy to treat MDR-TB. To uncover synergistic effects between the action of beta-lactams and the depletion of these PG modifications, knockdown mutants were also constructed in strains lacking the major beta-lactamase of M. smegmatis BlaS, PM965 (M. smegmatis ΔblaS1) and PM979 (M. smegmatis ΔblaS1 ΔnamH). The phenotyping assays affirmed the essentiality of the amidation of D-iso-glutamate to the survival of mycobacteria, as opposed to the N-glycolylation of muramic acid. The qRT-PCR assays confirmed the successful repression of the target genes, along with few polar effects and differential knockdown level depending on PAM strength and target site. Both PG modifications were found to contribute to beta-lactam resistance. While the amidation of D-iso-glutamate impacted cefotaxime and isoniazid resistance, the N-glycolylation of muramic acid substantially promoted resistance to the tested beta-lactams. Their simultaneous depletion provoked synergistic reductions in beta-lactam MICs. Moreover, the depletion of these PG modifications promoted a significantly faster bacilli killing by J774 macrophages. Whole-genome sequencing revealed that these PG modifications are highly conserved in a set of 172 clinical strains of Mtb, demonstrating their potential as therapeutic targets against TB. Our results support the development of new therapeutic agents targeting these distinctive mycobacterial PG modifications.